PEMBUKTIAN KESAKSIAN PALSU DI PERADILAN PIDANA DALAM KASUS KORUPSI E-KTP - Abram Reynnaldi (2021)
Giving false testimony in a trial is a criminal offense regulated by applicable law in Indonesia. This rule is contained in Article 242 of the Criminal Code which regulates perjury and false statements. In reality at trial there are still those who give false testimony with any purpose, so here it is necessary to have the role of the prosecutor and judge to prove and handle if it is true that the witness presented in the trial gave false testimony. In the criminal act of corruption, false information is regulated in Article 22 of Law no. 31 of 1999 in conjunction with Law no. 20 of 2001 so that there is a difference with false testimony in general crimes, this article can also be related to acts of obstruction of justice. The research method used in this study is normative juridical which in conducting the analysis uses library materials or secondary data as basic materials and provides an explanation of the legal provisions related to the issues raised.